Transcription profiles of boron-deficiency-responsive genes in citrus rootstock root by suppression subtractive hybridization and cDNA microarray - Zhou, Gao-Feng; Liu, Yong-Zhong; Sheng, Ou; Wei, Qing-Jiang; Yang, Cheng-Quan; Peng, Shu-Ang (Frontiers in Plant Science, 2015)
ABSTRACT Boron (B) deficiency has seriously negative effect on citrus production. Carrizo citrange (CC) has been reported as a B-deficiency tolerant rootstock. However, the molecular mechanism of its B-deficiency tolerance remained not well explored. To understand the molecular basis of citrus rootstock to B-deficiency, suppression subtractive hybridization (SSH) and microarray approaches were combined to identify the potential important or novel genes responsive to B-deficiency. Firstly four SSH libraries were constructed for the root tissue of two citrus rootstocks Carrizo citrange and Trifoliate orange (TO) to compare B-deficiency treated and non-treated plants. Then 7680 clones from these SSH libraries were used to construct a cDNA array and microarray analysis was carried out to verify the expression changes of these clones upon B-deficiency treatment at various time points compared to the corresponding controls. A total of 139 unigenes that were differentially expressed upon B-deficiency stress either in CC or TO were identified from microarray analysis, some of these genes have not previously been reported to be associated with B-deficiency stress. In this work, several genes involved in cell wall metabolism and transmembrane transport were identified to be highly regulated under B-deficiency stress, and a total of 23 metabolic pathways were affected by B-deficiency, especially the lignin biosynthesis pathway, nitrogen metabolism, and glycolytic pathway. All these results indicated that CC was more tolerant than TO to B-deficiency stress. The B-deficiency responsive genes identified in this study could provide further information for understanding the mechanisms of B-deficiency tolerance in citrus.